Thick-Film Based Piezoelectric Material Lead Zirconate Titanate (PZT) Performance Measurement Using Berlincourt Method - Kok, Swee Leong; Qumrul, Ahsan; Chang, Siang Yee (2012)
Lead Zirconate Titanate or PZT is a high performance piezoelectric material which is able to generate charges when a proportional amount of stress is applied on the material. It has the potential to be used to fabricate micro-power generator for powering low power electronic devices as well as smart structure to be function as sensors and actuators. One of the indicators for comparing the performance of the smart materials is the piezoelectric charge constant, d33. In this paper, the d33 of PZT fabricated in the form of thick-films were measured using Berlincourt Method whereby a standard dynamic force is applied to the materials and the resultant value of charges is recorded and compared over a period of time after the thick-films were polarized. The value is compared between clamped and unclamped samples which show a difference of about 45 % as a result of clamping effect. The experiment results also show that the thick-film PZT processed at 950 C and polarized at 220 V with a thickness of about 120 um has a piezoelectric charge constant of 82 pC/N.